γδ T cells and their clinical application in colon cancer - Corsale, Anna Maria; Di Simone, Marta; Lo Presti, Elena; Dieli, Francesco; Meraviglia, Serena (Frontiers in Immunology, 2023)
In recent years, research has focused on colorectal cancer to implement modern treatment approaches to improve patient survival. In this new era, gamma delta T cells constitute a new and promising candidate to treat many types of cancers thanks to their potent killing activity and their ability to recognize tumor antigens independently of HLA molecules, Here, we focus on the roles that gamma delta T cells play in anti-tumor immunity, especially in colorectal cancer. Furthermore, we provide an overview of small-scale clinical trials in patients with colorectal cancer employing either in vivo activation or adoptive transfer of ex vivo expanded gamma delta T cells, and suggest possible combinatorial approaches to treat colon cancer.